THE HUMAN IN HUMAN RESOURCES: BALANCING TECHNOLOGY WITH THE HUMAN TOUCH - Erin Kepria; Sri Langgeng Ratnasari; Alpino Susanto (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
The Human Resources function is undergoing a profound transformation driven by the rapid integration of technologies like artificial intelligence, data analytics, and automation. This shift promises unprecedented efficiency but also raises critical questions about the role of human judgment and connection in people management. This article investigates the imperative to balance technological adoption with the preservation of essential human elements within HR practices. It aims to develop a framework for synergistic integration where technology augments, rather than replaces, human capabilities. The research employs a qualitative, analytical methodology, synthesizing existing literature on HR technology, organizational psychology, and ethics. It analyzes contemporary case studies and industry trends to evaluate the impacts of this technological integration. The analysis confirms that while technology excels in administrative efficiency and data-driven insights, critical areas like complex communication, ethical judgment, culture-building, and strategic creativity remain irreplaceably human. A successful balance is achieved when technology handles transactional tasks, freeing HR professionals to focus on transformational, human-centric work. The future of HR lies not in choosing between technology and humanity, but in strategically leveraging technology to enhance the human touch. The most effective organizations will be those that use digital tools to empower HR professionals to become more empathetic, strategic, and ethical, thereby fostering a more engaged and resilient workforce.